2017
DOI: 10.1103/physrevx.7.041048
|View full text |Cite
|
Sign up to set email alerts
|

Gapless Symmetry-Protected Topological Order

Abstract: We introduce exactly solvable gapless quantum systems in d dimensions that support symmetry protected topological (SPT) edge modes. Our construction leads to long-range entangled, critical points or phases that can be interpreted as critical condensates of domain walls "decorated" with dimension (d − 1) SPT systems. Using a combination of field theory and exact lattice results, we argue that such gapless SPT systems have symmetry-protected topological edge modes that can be either gapless or symmetry-broken, l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(137 citation statements)
references
References 138 publications
6
125
0
Order By: Relevance
“…We now observe that, due to (16), the vertex operator e iπΦ(x) introduces a π kink in the phase Θ and hence from (17) it creates π kinks in the phases of all the flavors, θ a . We therefore conclude that switching the parity of all N chains simultaneously results in inserting a current N .…”
Section: Low-energy Description Of the Topological Phasementioning
confidence: 73%
“…We now observe that, due to (16), the vertex operator e iπΦ(x) introduces a π kink in the phase Θ and hence from (17) it creates π kinks in the phases of all the flavors, θ a . We therefore conclude that switching the parity of all N chains simultaneously results in inserting a current N .…”
Section: Low-energy Description Of the Topological Phasementioning
confidence: 73%
“…Another interesting extension to the interacting case was touched upon in Section 3.1.2. This suggested that the Z classification of gapped phases should be stable under interactions if we allow 24 We are grateful to the participants of the AIM workshop 'Fisher-Harwig asymptotics, Szegő expansions and statistical physics' for discussions on this point. 25 However, numerical simulations indicated the stability away from the non-interacting limit.…”
Section: Resultsmentioning
confidence: 99%
“…79, in the sense that operators charged under this symmetry in the bulk necessarily create gapped excitations (in this case, defects). The coexistence of gapless bulk with these additional gapped degrees of freedom ensures the twofold degeneracy of the ground state, up to an exponentially small finite size splitting [78,79]. In this particular model, due to the boundary SLIOMs, this degeneracy is exact (and present throughout the spectrum).…”
Section: Largest Sectors and Spt Ordermentioning
confidence: 99%